Robotic bariatric surgery: A general review of the current status. Issue 4 (23rd May 2017) - Jung, Minoa K.; Hagen, Monika E.; Buchs, Nicolas C.; Buehler, Leo H.; Morel, Philippe
Abstract: Background: While conventional laparoscopy is the gold standard for almost all bariatric procedures, robotic assistance holds promise for facilitating complex surgeries and improving clinical outcomes. Since the report of the first robotic‐assisted bariatric procedure in 1999, numerous publications, including those reporting comparative trials and meta‐analyses across bariatric procedures with a focus on robotic assistance, can be found. Purpose: This article reviews the current literature and portrays the perspectives of robotic bariatric surgery. Conclusions: While there are substantial reports on robotic bariatric surgery currently in publication, most studies suffer from low levels of evidence. As such, although robotics technology is without a doubt superior to conventional laparoscopy, the precise role of robotics in bariatric surgery is not yet clear.